STRATEGI PROBLEM-BASED LEARNING BERBANTUAN WORDWALL UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Agus Dede Anggiana; Emellia Giantbechtie Inggoesti; Vici Suciawati (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2026)
The purpose of this study was to determine the improvement of mathematical problem solving ability of students who obtained problem-based learning model assisted by Wordwall higher than students who obtained conventional learning model. The subjects in this study were even semester X grade students of SMK Pasundan 3 Bandung in the 2022/2023 school year, with the research sample using 2 classes, namely class X AKL 2 as the experimental class and class X AKL 1 as the control class. The research method used in this research is a quasi-experiment with a non-equivalent control group design. The instrument used in this study was a description of the mathematical problem solving ability test. The data obtained were then compared with the t-test. The results showed that the increase in mathematical problem solving ability of students who obtained the problem-based learning model assisted by Wordwall was higher than students who obtained the conventional learning model